Interleukin‐1 receptor‐associated kinase 4 inhibitor interrupts toll‐like receptor signalling and sensitizes chronic lymphocytic leukaemia cells to apoptosis. (14th February 2020) - Delvecchio, Vincenza Simona; Sana, Ilenia; Mantione, Maria Elena; Vilia, Maria Giovanna; Ranghetti, Pamela; Rovida, Alessandra; Angelillo, Piera; Scarfò, Lydia; Ghia, Paolo; Muzio, Marta
Summary: Chronic lymphocytic leukaemia (CLL) cells are strongly influenced by microenvironmental signals through the activation of distinct membrane receptors including the B‐cell receptor and toll‐like receptors (TLR). Recapitulating TLR stimulation in vitro by treating CLL cells with the TLR9 ligand CpG can induce metabolic activation and protection from apoptosis. We hypothesized that interfering with TLR signalling may be beneficial for treating CLL, and we tested in preclinical studies the effect of a specific interleukin‐1 receptor‐associated kinase 4 (IRAK4) inhibitory small molecule on primary leukaemic cells isolated from the peripheral blood of patients. We observed that IRAK4, an upstream kinase of the TLR pathway, is expressed in patients with CLL, and lower IRAK4 mRNA levels associate with a better outcome. The specific IRAK4 inhibitor disrupted TLR signalling as assessed by reduction of the specific biomarkers NFKBIZ and interleukin‐6 mRNAs, and restrained the protective effect of in vitro TLR stimulation on cell viability. To note, IRAK4 inhibitor induced p53 and triggered apoptosis. Co‐treatment of CLL cells with increasing concentrations of IRAK4i and the Bruton tyrosine kinase inhibitor ibrutinib demonstrated a synergistic effect. Our results suggest that targetting IRAK4 may represent a novel approach in CLL and may be combined with other signalling inhibitors.